Identifikasi Karakter Morfologi dan Analisis Kandungan Nutrisi Buah Pisang Mas, Buluh, dan Lumut Lokal Bali - I GUSTI AYU ARINI LAKSEMI; I NYOMAN RAI; NI NYOMAN ARI MAYADEWI (Agrotrop : Journal on Agriculture Science, 2023)
Identification of Morphological Characters and Fruits Nutrient Analysis of Pisang Mas, Buluh and Lumut Local Bali. Banana are a common commodity in Indonesia, having high economic, cultural and nutritional value. The objective of this research was to find the difference of morphological characters and nutrient content of Pisang Mas, Buluh and Lumut Local Bali. The research was conducted from July to October 2021. The samples of banana were taken from Antap Village, Selemadeg Barat District, Tabanan Regency, while identification and analysis were conducted in the laboratory. This research used UPGMA analysis and randomize complete design (RCD) with 3 replications. The results of identification showed different qualitative morphological characters in bunch position, fruit shape, fruit apex, remains of flower relicts at fruit apex, mature peel color, pedicel surface, pulp color before maturity, pulp color at maturity and predominant taste, while the quantitative showed the different in the number of pedicels, fruit length, fruit pedicel length and fruit peel thickness. Pulp nutrient content showed differences in water content, dry matter, crude lipid, crude fiber, and carbohydrate content.